2018
DOI: 10.1111/cmi.12946
|View full text |Cite
|
Sign up to set email alerts
|

Avian reovirus σA-modulated suppression of lactate dehydrogenase and upregulation of glutaminolysis and the mTOC1/eIF4E/HIF-1α pathway to enhance glycolysis and the TCA cycle for virus replication

Abstract: Adenosine triphosphate (ATP) is an energy source for many types of viruses for facilitating virus replication. This is the first report to demonstrate that the structural protein σA of avian reovirus (ARV) functions as an activator of cellular energy. Three cellular factors, isocitrate dehydrogenase 3 subunit beta (IDH3B), lactate dehydrogenase A (LDHA), and vacuolar-type H+-ATPase (vATPase) co-immunoprecipitated with ARV σA and were identified by 2D-LC/MS/MS. ARV enhances glycolytic flux through upregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…Data were evaluated for statistical significance according to Duncan's multiplerange test (DMRT) using SPSS software (version 20.0). The P values that were less than 0.05 were considered statistically significant (48).…”
Section: Discussionmentioning
confidence: 99%
“…Data were evaluated for statistical significance according to Duncan's multiplerange test (DMRT) using SPSS software (version 20.0). The P values that were less than 0.05 were considered statistically significant (48).…”
Section: Discussionmentioning
confidence: 99%
“…When nutrients become locally limited, several cancers, including pancreatic, glioblastoma, and ovarian, hijack stromal glutamine synthesis as an alternative supply line to fulfill their increased demands [13][14][15]. Furthermore, glutamine deprivation suppresses expansion of activated T lymphocytes, and competition for nutrients within tissues may affect immune responses to pathological states that exhibit hallmark increases in nutrient consumption (e.g., viral infection, cancer) [10,[16][17][18].…”
Section: Glutaminementioning
confidence: 99%
“…aerobic glycolysis and tumorigenic growth of NPC cells through activation of mTORC1/NF-kappaB signaling [65]. Avian reovirus structural protein sigmaA activates the mTOC1/eIF4E/ HIF-1α pathway to enhance glycolysis and the TCA cycle in the infected cells for virus replication [66]. In this study, we demonstrated that the phosphorylation of AMPK, a kinase that inhibits mTORC1 signaling [37,38], was down-regulated following HHV-6A infection ( S4 Fig), further supporting HHV-6 mediated-mTORC1 activation.…”
Section: Plos Pathogensmentioning
confidence: 99%